BnaMPK3 Is a Key Regulator of Defense Responses to the Devastating Plant Pathogen Sclerotinia sclerotiorum in Oilseed Rape - Wang, Zheng; Bao, Ling-Li; Zhao, Feng-Yun; Tang, Min-Qiang; Chen, Ting; Li, Yaoming; Wang, Bing-Xu; Fu, Benzhong; Fang, Hedi; Li, Guan-Ying; Cao, Jun; Ding, Li-Na; et al. (Frontiers in Plant Science, 2019)
The disease caused by Sclerotinia sclerotiorum has traditionally been difficult to control, resulting in tremendous economic losses in oilseed rape (Brassica napus). Identification of important genes in the defense responses is critical for molecular breeding, an important strategy for controlling the disease. Here, we report that a B. napus mitogen-activated protein kinase gene, BnaMPK3, plays an important role in the defense against S. sclerotiorum in oilseed rape. BnaMPK3 is highly expressed in the stems, flowers and leaves, and its product is localized in the nucleus. Furthermore, BnaMPK3 is highly responsive to infection by S. sclerotiorum and treatment with jasmonic acid (JA) or the biosynthesis precursor of ethylene (ET), but not to treatment with salicylic acid (SA) or abscisic acid. Moreover, overexpression (OE) of BnaMPK3 in B. napus and Nicotiana benthamiana results in significantly enhanced resistance to S. sclerotiorum, whereas resistance is diminished in RNAi transgenic plants. After S. sclerotiorum infection, defense responses associated with ET, JA and SA signaling are intensified in the BnaMPK3-OE plants but weakened in the BnaMPK3-RNAi plants when compared to those in the wild type plants; by contrast the level of both H2O2 accumulation and cell death exhibits a reverse pattern. The candidate gene association analyses show that the BnaMPK3-encoding BnaA06g18440D locus is a cause of variation in the resistance to S. sclerotiorum in natural B. napus population. These results suggest that BnaMPK3 is a key regulator of multiple defense responses to S. sclerotiorum, which may guide the resistance improvement of oilseed rape and related economic crops.